2017
DOI: 10.1002/hed.24659
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative iodine‐125 interstitial brachytherapy for the early stages of minor salivary gland carcinomas of the lip and buccal mucosa with positive or close margins

Abstract: Postoperative I seed interstitial brachytherapy is an alternative to radical surgery for early stages of minor salivary gland carcinomas of the lip and buccal mucosa, which offers satisfactory cosmetic and functional outcomes. © 2017 Wiley Periodicals, Inc. Head Neck 39: 572-577, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…As an internal RT, iodine-125 seed implantation has been successfully used to treat a series of malignant tumors, such as prostate cancer, 24 brain tumors, 25 , 26 pancreatic cancer, 27 skin cancer, 28 ovarian cancer, 29 recurrent cervical cancer, 30 and head and neck neoplasms, 31 especially in NSCLC. Santos et al indicated that the use of iodine-125 brachytherapy after sublobar resection significantly improved local control compared with sublobar resection alone (18.6 vs 2%; P <0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…As an internal RT, iodine-125 seed implantation has been successfully used to treat a series of malignant tumors, such as prostate cancer, 24 brain tumors, 25 , 26 pancreatic cancer, 27 skin cancer, 28 ovarian cancer, 29 recurrent cervical cancer, 30 and head and neck neoplasms, 31 especially in NSCLC. Santos et al indicated that the use of iodine-125 brachytherapy after sublobar resection significantly improved local control compared with sublobar resection alone (18.6 vs 2%; P <0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…External beam radiotherapy may be used to address this. However, in our patient, the tumor was small in size, was located superficially and there was no perineural invasion, so we felt comfortable using brachytherapy [7,8,[15][16][17][18][19]. The patient tolerated the procedure well with only grade two acute mucositis of the soft palate.…”
Section: Treatmentmentioning
confidence: 74%
“…Occasionally, brachytherapy is used in cancer centers with expertise in this modality to minimize toxicity in select cases of oropharyngeal and salivary gland cancers. The radiation dose to the normal tissues can be lowered by this method in select cases [15][16][17]. When tumors are technically accessible and superficially-located, surface mold brachytherapy technique may be utilized in oral and oropharyngeal cancers [7,8,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…125 I IBT, as a radiotherapy modality, increases local dose while sparing surrounding normal tissues, which is highly conformal, even for tumors closely surrounded by critical structures. 125 I IBT is increasingly being found to be effective for patients with head and neck malignant tumors and in improving LC and survival rate, so it is being used for pediatric soft‐tissue sarcoma treatment . Laskar et al treated 50 pediatric soft‐tissue sarcomas with brachytherapy as a monotherapy or combined with external radiotherapy.…”
Section: Discussionmentioning
confidence: 94%